3m-10=25-4m

Simple and best practice solution for 3m-10=25-4m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-10=25-4m equation:


Simplifying
3m + -10 = 25 + -4m

Reorder the terms:
-10 + 3m = 25 + -4m

Solving
-10 + 3m = 25 + -4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '4m' to each side of the equation.
-10 + 3m + 4m = 25 + -4m + 4m

Combine like terms: 3m + 4m = 7m
-10 + 7m = 25 + -4m + 4m

Combine like terms: -4m + 4m = 0
-10 + 7m = 25 + 0
-10 + 7m = 25

Add '10' to each side of the equation.
-10 + 10 + 7m = 25 + 10

Combine like terms: -10 + 10 = 0
0 + 7m = 25 + 10
7m = 25 + 10

Combine like terms: 25 + 10 = 35
7m = 35

Divide each side by '7'.
m = 5

Simplifying
m = 5

See similar equations:

| 7(7-x)=133 | | 6x+8=-40-2x | | 3x^2-45x=-168 | | 2x-5y-6z= | | 4.4x-7.8x=21.08 | | x+x+1+x+2+x=192 | | (.25)4y=5(.25) | | 2x+14=-11-3x | | 3x+2y=12y | | 15+g=27 | | 7y-11-10y+3=7 | | -1+49x=21x+43 | | 1/2*2+13=9 | | 9.2(+6.4)=132.48 | | t+13=18 | | -5q+9=-4q | | y=6*x | | x^2+(y^2)+z^2=z | | 5+2(x-3)=8+7 | | q-6=8 | | 18-5x=12-7x | | 2sin(x)tan(x)=3 | | 4x-3y-12z= | | 28y-1=5 | | 5-4y=8 | | 4x^3+4x-4=0 | | 7y-11-10y+3= | | 25+0.05n=7+0.11n | | 4x^3+4x=4 | | 647=6x-99.4 | | 5x-7=4x+36 | | 12g-(-7)=31 |

Equations solver categories